The Indonesian version of irrational beliefs tests in rational emotive behavior therapy: adaptation of irrational beliefs tests - Margaretha, Maria; Hastuti, Sri (COUNS-EDU: The International Journal of Counseling and Education, 2017)
This Indonesian version of Irrational Beliefs Test (IV-IBT) measures the irrational thoughts in accordance with the irrational belief’s concept by Albert Ellis (Rational Emotive Behavior Therapy) and is the result from the language and cultural adaptation of Irrational Beliefs Test (IBT; Richard Garner Jones, 1968). There are 10 irrational thoughts contained in IBT namely demand for approval, high self-expectation, blame proneness, frustration reactive, anxious overcome, problem avoidance, dependency, helplessness, perfectionism. IBT consists of 100 items originating from 10 items for each type of irrational thoughts. The IBT adaptation process was conducted using the Guidelines for test translations (van de Vijver & Hambleton, 1996), and further elaborated into four major steps, namely (1) the translation from English into Indonesian by an expert in English language and a psychologist, and from Indonesian into English by two experts in English language, (2) content validity assessment by three assessors who master the REBT concepts and psychological measurement, (3) dimensionality examination with exploratory factor analysis, (4) empirical testing to obtain the accurate, adequate, and relevant item formulation involving 302 students. The Irrational Beliefs Test consists of 31 items, 10 factors, and is unidimensional (single dimension) in nature. Results and discussion are described in the Indonesian culture context.